2002
DOI: 10.1097/00003072-200202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Specific-Activity Sulfur Colloid Preparations on Sentinel Node Count Rates

Abstract: These preliminary results suggest higher counts in the sentinel node are possible with a higher SA preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In addition, larger particles would limit the number of echelon nodes (nodes downstream of the first SN) seen along the lymphatic chain, although it has been suggested that harvesting echelon nodes along with the SN decreases the false-negative rate (12)(13)(14). A high specific activity preparation has been reported to further improve performance (15,16). Tc-99m nanocolloid, which is used outside the United States, has a much smaller average particle range, with almost all particles less than 100 nm in diameter (8).…”
Section: Radiopharmaceutical Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, larger particles would limit the number of echelon nodes (nodes downstream of the first SN) seen along the lymphatic chain, although it has been suggested that harvesting echelon nodes along with the SN decreases the false-negative rate (12)(13)(14). A high specific activity preparation has been reported to further improve performance (15,16). Tc-99m nanocolloid, which is used outside the United States, has a much smaller average particle range, with almost all particles less than 100 nm in diameter (8).…”
Section: Radiopharmaceutical Preparationmentioning
confidence: 99%
“…A topical anesthetic has worked well for us. EMLA cream alone (lidocaine 2.5% and prilocaine 2.5%; Astra Pharmaceuticals, Wayne, Pa) has proved to be effective in controlling local surface pain during injections for all but areolar-cutaneous junction injections (11,16). The cream needs to be applied to the skin for at least 20 -30 minutes to be fully effective.…”
Section: Pain Controlmentioning
confidence: 99%
“…Effect of specific activity of the Tc99m elute for kit preparation on the success of sentinel node mapping has been evaluated in several studies before. [27][28][29][30] Major results of these studies can be found in Table 2. All four previous studies on this topic showed that increased sentinel node count rate can be achieved by increasing the specific activity of the Tc-99m elute (by using 2-hour elute vs. 24-hour elute, using a proportion of a kit, or using a lower volume of Tc-99m for kit preparation).…”
Section: Discussionmentioning
confidence: 99%
“…With time however, such nonspecific trapping will allow the release of particles for subsequent migration to other "downstream" nodes [78]. Krynyckyi et al [80] demonstrated that colloidal preparations with higher specific activity demonstrated higher retention (of radioactivity) within sentinel nodes than preparations with lower specific activity, consistent with the concept of a limited capacity for phagocytic uptake within a single node.…”
Section: Colloids In Lymphaticsmentioning
confidence: 99%